Length of Aging has Greater Effect than Lactic Acid Treatment on Color Stability of Beef Chuck Muscles - G. D. McCoy; T. A. Houser; T. G. O'Quinn; E. A. Boyle; K. J. Phelps; J. M. Gonzalez (Kansas Agricultural Experiment Station Research Reports, 2017)
Lactic acid spray washes are widely used as an antimicrobial intervention in the beef industry. Sprays are typically applied to the exterior of carcasses and subprimal cuts to reduce or eliminate potential pathogenic bacteria. While the efficacy of these washes has been proven, other questions remain about their effect on color attributes of meat when applied to subprimal cuts. The objective of this study was to determine the effect of a lactic acid subprimal wash on the color stability of beef chuck rolls.
Keywords: beef chuck muscles; lactic acid; color stability